Clinical Profile and Etiology of Children Presenting with Prolonged Fever: A Study in Tertiary Care Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Children often undergo medical evaluation for fever, which can be difficult to diagnose as serious infection or viral illness. Fever of unknown origin (FUO) is categorized within prolonged fever lasts at least 14 days.Objectives: This study aimed to find a clinical and etiologic profile of children presenting with prolonged fever in tertiary care hospital in Bangladesh.Methods: This prospective observational study was conducted at the Department of Pediatrics, Monno Medical College and Hospital, Manikganj, Bangladesh from January 2020 to July 2021. A total of 100 children with fever for seven days or more were enrolled as the study subjects using a purposive sampling technique.Results: In this study, 55% of participants were aged 3-10 years, with a male-female ratio of 1.8:1. Most patients (69%) were well-nourished. All participants had fever, while 43% experienced vomiting, 32% abdominal pain, 24% cough, and 16% headache. Clinical findings included coated tongue (36%), hepatosplenomegaly (24%), isolated hepatomegaly (12%), and eschar marks (10%). The causes of prolonged fever identified were enteric fever (42%), rickettsia (21%), UTI (13%), combined enteric fever and UTI (8%), and pneumonia (7%).Conclusion: Male children aged 3 to 10 years are particularly prone to prolonged fever, regardless of nutritional status. Common symptoms include vomiting, abdominal pain, cough, headache, coated tongue, and hepatosplenomegaly. Potential causes of prolonged fever in children include enteric fever, rickettsia, and urinary tract infections.Journal of National Institute of Neurosciences Bangladesh, July 2024;10(2):104-109